A cross-linked anion exchange membrane, a preparation method and application thereof
Patent Information
- Application Number
- CN202611390494.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-09
- Publication Date
- 2026-10-13
AI Technical Summary
然而,现有AEM仍普遍存在离子分离效率偏低、运行稳定性不足以及使用寿命较短等问题,突出表现为离子传导率较低、膜电阻较高和耐久性较差,如何提升AEM的离子传导性能、降低膜电阻并增强其长期运行可靠性,已成为该技术领域亟需攻克的技术难题
[0038]本发明利用不同高分子聚合物在热力学性质、亲疏水特性及能垒等方面的差异,通过自由基交联策略,制备了一系列交联型阴离子交换膜。在传统电渗析用聚氯乙烯、聚砜、聚醚砜等聚合物材料的基础上,引入自主合成的含烯烃侧链的聚芳基哌啶聚合物,并借助Menshutkin反应接枝引入咪唑、哌啶、三甲胺等阳离子基团进行改性,最终获得了具有低面电阻、高离子传导率的柔性交联型阴离子交换膜。
Smart Images

Figure CN122898010A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of ion exchange membrane material technology, specifically relating to a cross-linked anion exchange membrane, its preparation method, and its application. Background Technology
[0002] Electrodialysis, as a highly efficient and green membrane separation method, relies on the ion-selective permeability of ion exchange membranes and the ion migration mechanism driven by an electric field to achieve precise separation and purification of target ions in solution. It can effectively promote near-zero discharge of industrial wastewater and realize the resource utilization of high-salt wastewater.
[0003] Anion exchange membranes (AEMs), as one of the core components of electrodialysis devices, possess advantages such as high ion selectivity, mild operating conditions, and relatively low cost. They mainly perform the following three functions: (1) providing a directional transport channel for counterions to achieve precise ion separation; (2) serving as an isolation barrier between the desalination chamber and the concentration chamber to prevent cross-flow of feed solutions between the two chambers; and (3) preventing the migration of common ions from the concentration chamber to the desalination chamber to avoid common ion leakage. However, existing AEMs still generally suffer from problems such as low ion separation efficiency, insufficient operational stability, and short service life. These problems are mainly manifested in low ion conductivity, high membrane resistance, and poor durability. How to improve the ion conductivity of AEMs, reduce membrane resistance, and enhance their long-term operational reliability has become a technical challenge that urgently needs to be overcome in this field. Summary of the Invention
[0004] To address the aforementioned technical problems, the present invention aims to provide a cross-linked anion exchange membrane, its preparation method, and its applications.
[0005] To achieve the above objectives, the technical solution adopted by the present invention is as follows:
[0006] A cross-linked anion exchange membrane is obtained by cross-linking quaternized polyarylepiperidine containing olefin side chains with a modified polymer, and its structure is shown in the general formula:
[0007] Where n = 1~6, x = 10%~25%;
[0008] Ar represents biphenyl, para-terphenyl, meta-terphenyl, or fluorene;
[0009] Polymers are polyvinyl chloride, polyethersulfone, polysulfone, polyphenylene ether, polyetheretherketone or polyarylpiperidine;
[0010] QA is trimethylamine, N-methylpiperidine, N-methylpyrrole, N-methylimidazolium or pyridine;
[0011] The anion is OH -Cl - Or I - .
[0012] A further improvement to the technical solution of the present invention is that x takes the value of 10%, 15%, 20% or 25%.
[0013] A further improvement of the technical solution of the present invention is that the quaternized polyarylepiperidine containing olefin side chains is obtained by polycondensation of biphenyl monomers with 1-methyl-4-piperidinone to obtain polyarylepiperidine, and then quaternized after grafting with halogenated olefins; the biphenyl monomers are selected from one of biphenyl, m-terphenyl, p-terphenyl or fluorene.
[0014] The modified polymer is obtained by grafting alkenyl imidazole onto a polymer backbone and then quaternizing it. The polymer backbone is selected from one of polyvinyl chloride, polyethersulfone polymers, polysulfone polymers, polyphenylene ether polymers, polyether ether ketone polymers, or polyarylpiperidine polymers.
[0015] A further improvement to the technical solution of the present invention is that it includes the following steps:
[0016] 1) Dissolve biphenyl monomers in solvent A, add 1-methyl-4-piperidinone and catalyst sequentially, react at 0°C to obtain a viscous liquid, precipitate and wash to obtain polyarylpiperidine, and dry for later use;
[0017] 2) Dissolve the polyarylpiperidine obtained in step 1) in solvent B, add haloolefin and potassium carbonate, react under heating conditions, and after the reaction is complete, precipitate with solvent to obtain polyarylpiperidine containing olefin side chains.
[0018] 3) Dissolve the polyarylpiperidine containing olefin side chains obtained in step 2) in solvent C, add iodomethane, react in the dark, and after the reaction is complete, precipitate with solvent to obtain quaternized polyarylpiperidine containing olefin side chains.
[0019] 4) Dissolve the polymer backbone in solvent D, add alkenyl imidazole monomers and potassium carbonate, react under heating conditions, and after the reaction is complete, precipitate with solvent to obtain the modified polymer backbone-imidazole.
[0020] 5) Dissolve the product obtained in step 4) in solvent E, add quaternizing reagent, react at room temperature, and after the reaction is completed, precipitate with solvent to obtain the modified polymer;
[0021] 6) Dissolve the quaternized polyarylepiperidine with olefin side chains obtained in step 3) and the modified polymer obtained in step 5) in solvent F, add initiator 2,2-azobisisobutyronitrile to obtain a homogeneous casting solution, and cast it into a film; after film formation, perform anion exchange to obtain the cross-linked anion exchange membrane.
[0022] A further improvement of the technical solution of the present invention is that solvent A is selected from one of dichloromethane, 1,2-dichloroethane and trichloromethane; solvents B to F are each selected from at least one of dimethyl sulfoxide, N-methylpyrrolidone, N,N-dimethylformamide and N,N-dimethylacetamide.
[0023] A further improvement to the technical solution of the present invention is that the viscous liquid in step 1) is precipitated with a sodium hydroxide solution with a concentration of 1~3 mol / L;
[0024] In steps 2) and 3), the precipitation solvent is selected from at least one of n-hexane, cyclohexane, ethyl acetate, and tert-butyl methyl ether;
[0025] In steps 4) and 5), the precipitation solvent is selected from at least one of methanol, ethanol and acetonitrile.
[0026] A further improvement of the technical solution of the present invention is that the haloalkene in step 2) is selected from one of bromopropene, 4-bromo-1-butene, 5-bromo-1-pentene, 6-bromo-1-hexene, 7-bromo-1-heptene and 8-bromo-1-octene;
[0027] The alkenyl imidazolium monomer mentioned in step 4) is selected from one of 1-vinylimidazolium and N-propenylimidazolium;
[0028] The quaternizing agent mentioned in step 5) is selected from one of trimethylamine, N-methylpiperidine, N-methylpyrrole, N-methylimidazolium and pyridine.
[0029] A further improvement of the technical solution of the present invention is that, in step 1), the molar ratio of the biphenyl monomer to 1-methyl-4-piperidinone is 1:(1~1.5);
[0030] In step 2), the molar ratio of polyarylpiperidine to haloalkene is 1:(0.25~0.5); the reaction temperature is 80℃ and the reaction time is 24~48h.
[0031] In step 3), the molar ratio of polyarylpiperidine containing olefin side chains to iodomethane is 1:(1~1.3); the reaction time is 24~72h;
[0032] In step 4), the molar ratio of the polymer backbone to the alkenyl imidazole monomer is 1:(0.25~0.5), the reaction temperature is 80℃, and the reaction time is 24~48h.
[0033] In step 5), the molar ratio of the modified polymer backbone-imidazole to the quaternizing agent is 1:(0.25~0.5), the reaction temperature is room temperature, and the reaction time is 24~48h;
[0034] In step 6), the molar ratio of the quaternized polyarylepiperidine with olefin side chains obtained in step 3) to the modified polymer obtained in step 5) is 1:(1~1.2).
[0035] A further improvement of the technical solution of the present invention is that the catalyst in step 1) is trifluoroacetic acid and trifluoromethanesulfonic acid, and the molar ratio of the biphenyl monomer, trifluoroacetic acid and trifluoromethanesulfonic acid is 1:(1~1.3):(1~10).
[0036] The present invention also discloses the application of the cross-linked anion exchange membrane in the field of electrodialysis.
[0037] Due to the adoption of the above technical solution, the beneficial effects of the present invention are as follows:
[0038] This invention utilizes the differences in thermodynamic properties, hydrophilicity / hydrophobicity, and energy barriers among various polymers to prepare a series of cross-linked anion exchange membranes through a free radical cross-linking strategy. Based on traditional electrodialysis polymers such as polyvinyl chloride, polysulfone, and polyethersulfone, a self-synthesized polyarylpiperidine polymer containing olefin side chains is introduced. Furthermore, imidazole, piperidine, and trimethylamine cationic groups are grafted onto the polymer using the Menshutkin reaction for modification, ultimately yielding flexible cross-linked anion exchange membranes with low surface resistivity and high ionic conductivity.
[0039] This invention utilizes the differences in thermodynamic, hydrophilic / hydrophobic, and energy barrier properties of different polymers to effectively promote the formation of hydrophilic / hydrophobic microphase separation structures, alleviate dead-end effects in ion transport, accelerate ion transport and separation processes, thereby reducing membrane surface resistance and energy consumption in electrodialysis operation.
[0040] The introduction of polyarylepiperidine polymers in this invention can form π-π stacked structures, enhance the self-assembly ability between polymer chains, facilitate the construction of efficient ion transport channels, and improve ion conductivity.
[0041] This invention is based on a crosslinking strategy using different phenyl-containing polymers to prepare a crosslinked anion exchange membrane with both high ionic conductivity and low membrane surface resistance, which effectively improves the electrodialysis performance of the anion exchange membrane and has broad application prospects in the field of electrodialysis. Attached Figure Description
[0042] Figure 1 This is a schematic flowchart of the preparation method of Embodiment 2 of the present invention;
[0043] Figure 2 This is a graph showing the relationship between conductivity and temperature of the products of Examples 1-3 and Comparative Examples 1-3 of the present invention;
[0044] Figure 3This is a graph showing the ion transport number and surface resistivity data of the products of Examples 1-3 and Comparative Examples 1-3 of the present invention;
[0045] Figure 4 This is the infrared spectrum of the product from Example 1. Detailed Implementation
[0046] The present invention will be further described below with reference to embodiments. It should be understood that the preferred embodiments described herein are for illustrative and understanding purposes only and are not intended to limit the scope of the invention.
[0047] Unless otherwise specified, all raw materials used in the embodiments of the present invention are commercially available, all equipment used are conventional equipment in this technical field, and all methods used are conventional methods in this technical field.
[0048] Example 1
[0049] This embodiment describes a method for preparing a quaternized poly(biphenylpiperidine)-polyvinyl chloride imidazole crosslinked anion exchange membrane, specifically including the following steps:
[0050] 1) Preparation of the polyphenylpiperidine backbone
[0051] 5.0 g (32.4 mmol) of biphenyl was poured into a dry 250 mL round-bottom flask equipped with a magnetic stir bar. 5.0 mL of dichloromethane was added and dissolved completely. Then, 5.20 mL (45.6 mmol) of 1-methyl-4-piperidinone was added at 0 °C. Subsequently, 2.40 mL (32.4 mmol) of trifluoroacetic acid and 28.70 mL (324.0 mmol) of trifluoromethanesulfonic acid were slowly added sequentially to initiate the polymerization reaction. The reaction was magnetically stirred for 4 hours. After the reaction was complete, 200 mL of 2 mol / L NaOH solution was added to the reaction system to precipitate the product. The product was filtered under reduced pressure to obtain a solid product, which was then washed with deionized water until the washings were neutral, yielding polybiphenylpiperidine wet powder. The obtained polybiphenylpiperidine wet powder was dried in a 60 °C oven for 5 hours for later use.
[0052] 2) Preparation of poly(piperidine-pentene)
[0053] 4.0 g (16.0 mmol) of polybiphenylpiperidine prepared in step 1) was added to a dry round-bottom flask equipped with a magnetic flask, and 20.0 mL of N-methylpyrrolidone was added. After the polybiphenylpiperidine dissolved, 1.00 g (6.7 mmol) of 5-bromo-1-pentene and 0.20 g (1.4 mmol) of potassium carbonate were added. The mixture was reacted at 80 °C for 48 h. After the reaction was complete, the dark brown solution in the flask was slowly poured into 300 mL of ethyl acetate solution to precipitate the product. The product was then filtered and washed three times with deionized water to obtain polybiphenylpiperidine-pentene.
[0054] 3) Preparation of quaternized polyphenylpiperidine-pentene
[0055] Take 2.0 g (7.4 mmol) of polybiphenylpiperidine-pentene prepared in step 2) and add it to a dry round-bottom flask equipped with a magnetic flask. Add 10.0 mL of dimethyl sulfoxide and dissolve it completely. Then add 0.60 mL (9.6 mmol) of iodomethane and react at room temperature in the dark for 48 h. After the reaction is complete, slowly pour the dark brown solution in the flask into 300 mL of ethyl acetate to precipitate the product. Then filter the product and wash it three times with deionized water to obtain quaternized polybiphenylpiperidine-pentene.
[0056] 4) Preparation of polyvinyl chloride-imidazolium
[0057] 4.0 g (64.0 mmol) of polyvinyl chloride was dissolved in 20.0 mL of N-methylpyrrolidone. After complete dissolution, 2.03 mL (22.4 mmol) of 1-vinylimidazole and 0.10 g (0.7 mmol) of potassium carbonate were added. The mixture was reacted at 80 °C for 48 h. After the reaction was complete, the dark yellow solution in the flask was slowly poured into 200 mL of methanol to precipitate the product. The product was then filtered and washed three times with deionized water to obtain polyvinyl chloride-imidazole.
[0058] 5) Preparation of Quaternized Polyvinyl Chloride-Imidazole
[0059] Take 2.0 g (28.0 mmol) of polyvinyl chloride-imidazolium prepared in step 4) and dissolve it in 10.0 mL of N-methylpyrrolidone. After complete dissolution, add 3.30 mL (14.0 mmol) of 30% trimethylamine aqueous solution and react at room temperature for 24 h. After the reaction is complete, slowly pour the yellow solution in the flask into 200 mL of methanol to precipitate. Then filter the product and wash it three times with deionized water to obtain quaternized polyvinyl chloride-imidazolium polymer.
[0060] 6) Preparation of quaternized polybenzylpiperidine-polyvinyl chloride imidazole crosslinked anion exchange membrane
[0061] Take 1.0 g (3.6 mmol) of quaternized polybis(piperidine-pentene) prepared in step 3) and 0.34 g (3.6 mmol) of quaternized polyvinyl chloride-imidazolium prepared in step 5), dissolve them in 20 mL of a mixed solution of dimethyl sulfoxide and N-methylpyrrolidone in a volume ratio of 1:1, add 0.02 g of 2,2-azobisisobutyronitrile, and cast the mixture at 80 °C to form a film. The structural formula of the resulting film is:
[0062] After film formation, the sample was divided into two equal parts and immersed in 0.5 mol / L NaCl solution and 1 mol / L NaOH solution, respectively, for 24 hours for anion exchange. Subsequently, both membranes were removed and washed three times with deionized water to obtain Cl₂. - Type film and OH - Type membrane.
[0063] Example 1 above illustrates the present invention using biphenyl as an example. Biphenyl, para-terphenyl, meta-terphenyl, and fluorene all possess a biphenyl core structure, and their molecular skeletons exhibit similar rigidity, π-π conjugation ability, and steric hindrance. In this invention, their reaction mechanisms and physicochemical behaviors are consistent. Based on the above principles, those skilled in the art can substitute the described biphenyl monomers for each other without creative effort and can reasonably expect them to achieve essentially the same technical effects; therefore, they will not be listed individually here.
[0064] Example 2
[0065] This embodiment describes a method for preparing a quaternized poly(biphenylpiperidine)-polysulfonamide crosslinked anion exchange membrane, such as... Figure 1 As shown, the specific steps include:
[0066] Steps 1) to 3) are the same as steps 1) to 3) in Example 1;
[0067] 4) Preparation of polysulfone-imidazolium
[0068] 4.0 g (8.7 mmol) of chloromethylated polysulfone was dissolved in 20.0 mL of N-methylpyrrolidone. After complete dissolution, 0.40 mL (4.3 mmol) of 1-vinylimidazole was added. The mixture was reacted at 80 °C for 36 h. After the reaction was complete, the light yellow solution in the flask was slowly poured into 200 mL of methanol to precipitate the product. The product was filtered and washed three times with deionized water to obtain white polysulfone-imidazole.
[0069] 5) Preparation of quaternized polysulfone-imidazole
[0070] Take 2.0 g (4.0 mmol) of polysulfone-imidazolium prepared in step 4) and dissolve it in 10.0 mL of N-methylpyrrolidone. After complete dissolution, add 0.40 mL (1.7 mmol) of 30% trimethylamine aqueous solution and react at room temperature for 36 h. After the reaction is complete, slowly pour the yellow solution in the flask into 200 mL of methanol to precipitate. Filter the product and wash it three times with deionized water to obtain quaternized polysulfone-imidazolium.
[0071] 6) Preparation of quaternized polybenzylpiperidine-polysulfonamide crosslinked anion exchange membrane
[0072] Take 1.0 g (3.6 mmol) of quaternized polybis(piperidine-pentene) prepared in step 3) and 2.10 g (3.6 mmol) of quaternized polysulfone-imidazolium prepared in step 5), dissolve them in 20 mL of a mixed solution of dimethyl sulfoxide and N-methylpyrrolidone in a volume ratio of 1:1, add 0.02 g of 2,2-azobisisobutyronitrile initiator, and cast the mixture at 80 °C to form a film. The structural formula of the resulting film is:
[0073] After film formation, the sample was divided into two equal parts and immersed in 0.5 mol / L NaCl solution and 1 mol / L NaOH solution, respectively, for 24 hours for anion exchange. Subsequently, both membranes were removed and washed three times with deionized water to obtain Cl₂. - Type film and OH - Type membrane.
[0074] Example 3
[0075] This embodiment describes a method for preparing a quaternized poly(biphenylpiperidine)-polyethersulfone imidazole crosslinked anion exchange membrane, specifically including the following steps:
[0076] The preparation of steps 1) to 3) is the same as that of steps 1) to 3) in Example 1.
[0077] 4) Preparation of polyethersulfone-imidazole
[0078] 4.0 g (14.3 mmol) of chloromethylated polyethersulfone was dissolved in 20 mL of N-methylpyrrolidone. After complete dissolution, 0.63 mL (7.0 mmol) of 1-vinylimidazole was added, and the mixture was reacted at 80 °C for 24 h. After the reaction was complete, the light yellow solution in the flask was slowly poured into 200 mL of methanol to precipitate the product. The product was filtered and washed three times with deionized water to obtain white polyethersulfone-imidazole.
[0079] 5) Preparation of quaternized polyethersulfone-imidazole
[0080] Take 2.0 g (6.8 mmol) of polyethersulfone-imidazolium prepared in step 4) and dissolve it in 10 mL of N-methylpyrrolidone. After complete dissolution, add 0.60 mL (2.5 mmol) of 30% trimethylamine aqueous solution and react at room temperature for 48 h. After the reaction is complete, slowly pour the light yellow solution in the flask into 200 mL of methanol to precipitate. Filter the product and wash it three times with deionized water to obtain quaternized polyethersulfone-imidazolium.
[0081] (6) Preparation of quaternized polybisphenylpiperidine-polyethersulfone imidazole crosslinked anion exchange membrane
[0082] Take 1.0 g (3.6 mmol) of quaternized polybis(piperidine-pentene) prepared in step 3) and 1.2 g (3.6 mmol) of quaternized polyethersulfone-imidazolium prepared in step 5), dissolve them in 20 mL of a mixed solution of dimethyl sulfoxide and N-methylpyrrolidone in a volume ratio of 1:1, add 0.02 g of 2,2-azobisisobutyronitrile initiator, and cast the mixture at 80 °C to form a film. The structural formula of the resulting film is:
[0083] After film formation, the sample was divided into two equal parts and immersed in 0.5 mol / L NaCl solution and 1 mol / L NaOH solution, respectively, for 24 hours for anion exchange. Subsequently, both membranes were removed and washed three times with deionized water to obtain Cl₂. - Type film and OH - Type membrane.
[0084] Examples 1-3 above illustrate the present invention using polyvinyl chloride, chloromethylated polysulfone, and chloromethylated polyethersulfone as examples. Polyphenylene ether polymers and polyether ether ketone polymers can be modified by chloromethylation, and subsequently quaternization to complete cationic grafting. Polyarylpiperidine polymers can directly complete cationic grafting and modification. The reaction principles of the three types of substances are similar to those in Examples 1, 2, and 3. Those skilled in the art can substitute the biphenyl monomers for each other without creative effort and can reasonably expect them to achieve essentially the same technical effect. They will not be listed one by one here.
[0085] Examples 4-7 are methods for preparing quaternized polybiphenylpiperidine-polyvinyl chloride imidazole crosslinked anion exchange membranes. The operation steps are similar to those in Example 1, except for the types and amounts of reactants and the control parameters in the process. The resulting product structures are slightly different. The specific products of Examples 4-7 are quaternized polybiphenylpiperidine-propylene-polyvinyl chloride-propylene imidazole, quaternized polybiphenylpiperidine-butene-polyvinyl chloride-vinyl imidazole, quaternized polybiphenylpiperidine-heptene-polyvinyl chloride-propylene imidazole, and quaternized polybiphenylpiperidine-octene-polyvinyl chloride-vinyl imidazole, respectively.
[0086] See Tables 1 and 2 below for details:
[0087] Table 1
[0088] Table 2
[0089] Comparative Example 1
[0090] This comparative example illustrates a method for preparing a quaternized polyvinyl chloride-imidazolium crosslinked anion exchange membrane, specifically including the following steps:
[0091] 1) Preparation of polyvinyl chloride-imidazolium
[0092] Same as step 4 in Example 1.
[0093] 2) Preparation of quaternized polyvinyl chloride-imidazole
[0094] Same as step 5 in Example 1.
[0095] 3) Preparation of quaternized polyvinyl chloride imidazole crosslinked anion exchange membrane
[0096] Take 1.0 g of quaternized polyvinyl chloride-imidazolium prepared in step 2), dissolve it in 20 mL of a mixed solution of dimethyl sulfoxide and N-methylpyrrolidone in a volume ratio of 1:1, add 0.02 g of 2,2-azobisisobutyronitrile initiator, and cast it into a film at 80 °C.
[0097] After film formation, the sample was divided into two equal parts and immersed in 0.5 mol / L NaCl solution and 1 mol / L NaOH solution, respectively, for 24 hours for anion exchange. Subsequently, both membranes were removed and washed three times with deionized water to obtain Cl₂. - Type film and OH - Type membrane.
[0098] Comparative Example 2
[0099] This comparative example illustrates the preparation method of a quaternized polysulfone-imidazolium crosslinked anion exchange membrane, specifically including the following steps:
[0100] 1) Preparation of polysulfone-imidazolium
[0101] Same as step 4) in Example 2.
[0102] 2) Preparation of quaternized polysulfone-imidazole
[0103] Same as step 5 in Example 2.
[0104] 3) Preparation of quaternized polysulfonyl imidazole crosslinked anion exchange membrane
[0105] Take 1.0g of the quaternized polysulfone-imidazolium prepared in step 2), dissolve it in 20mL of a mixed solution of dimethyl sulfoxide and N-methylpyrrolidone in a volume ratio of 1:1, add 0.02g of 2,2-azobisisobutyronitrile initiator, and cast it into a film at 80℃.
[0106] After film formation, the sample was divided into two equal parts and immersed in 0.5 mol / L NaCl solution and 1 mol / L NaOH solution, respectively, for 24 hours for anion exchange. Subsequently, both membranes were removed and washed three times with deionized water to obtain Cl₂. - Type film and OH - Type membrane.
[0107] Comparative Example 3
[0108] This comparative example illustrates the preparation method of a quaternized polyethersulfone-imidazolium crosslinked anion exchange membrane, specifically including the following steps:
[0109] 1) Preparation of polyethersulfone-imidazolium
[0110] Same as step 4) in Example 3.
[0111] 2) Preparation of quaternized polyethersulfone-imidazole
[0112] Same as step 5 in Example 3.
[0113] 3) Preparation of quaternized polyethersulfone imidazole crosslinked anion exchange membrane
[0114] Take 1.0g of the quaternized polyethersulfone-imidazolium prepared in step 2), dissolve it in 20mL of a mixed solution of dimethyl sulfoxide and N-methylpyrrolidone in a volume ratio of 1:1, add 0.02g of 2,2-azobisisobutyronitrile initiator, and cast it into a film at 80℃.
[0115] After film formation, the sample was divided into two equal parts and immersed in 0.5 mol / L NaCl solution and 1 mol / L NaOH solution, respectively, for 24 hours for anion exchange. Subsequently, both membranes were removed and washed three times with deionized water to obtain Cl₂. - Type film and OH - Type membrane.
[0116] Performance testing:
[0117] The OH groups prepared in Examples 1-3 and Comparative Examples 1-3 were analyzed using AC impedance spectroscopy with a conventional electrochemical workstation. - The ionic conductivity of the anion exchange membrane was tested, with a scanning frequency range of 10~105 Hz, and its ionic conductivity-temperature variation graph was obtained, as shown below. Figure 2 As shown; tests showed that the conductivity of the membrane in Example 1 reached 139.59 mS / cm at 80°C. -1 Example 2: The membrane conductivity can reach 106.55 mS / cm. -1 In Example 3, the conductivity of the membrane reached 111.36 mS / cm. -1The conductivity of the membrane in Comparative Example 1 was only 47.10 mS / cm. -1 The conductivity of the membrane in Comparative Example 2 was 92.63 mS / cm. -1 The conductivity of the membrane in Comparative Example 3 was 95.74 mS / cm. -1 .
[0118] Using a direct current and a self-made film resistance testing device, the Cl prepared in Examples 1-3 and Comparative Examples 1-3 were tested at room temperature. - Sheet resistance and ion mobility number were measured on a type of anion exchange membrane, and the sheet resistance and ion mobility number data were obtained, as shown in the figure. Figure 3 As shown; the sheet resistivity of the membrane in Example 1 was tested to be 1.64 Ω cm. 2 The ion transport number is 0.985; the sheet resistivity of the film in Example 2 is 1.88 Ω cm. 2 The ion transport number was 0.974; the sheet resistivity of the film in Example 3 was 1.72 Ω cm. 2 The ion transport number was 0.982; the sheet resistivity of the film in Comparative Example 1 was 7.32 Ω cm⁻¹. 2 The ion transport number was 0.833; the sheet resistivity of the film in Comparative Example 2 was 2.88 Ω cm. 2 The ion transport number was 0.958; the sheet resistivity of the film in Comparative Example 3 was 2.56 Ω cm⁻¹. 2 The ion transport number is 0.965.
[0119] Infrared spectral scanning of Example 1 was performed using a Shimadzu infrared spectrometer, such as... Figure 4 As shown, at 2932cm -1 With 2731cm -1 The characteristic peak of -CH2- after crosslinking of polyvinyl chloride and olefins appears at 1643 cm⁻¹. -1 and 1427cm -1 The characteristic peak at 1334 cm⁻¹ belongs to the stretching vibration peak of the benzene ring skeleton. -1 The absorption peak at 1255 cm⁻¹ is attributed to the bending vibration of the -CH group bonded to N in the quaternary ammonium structure. -1 The characteristic peaks at the specified locations are attributed to the stretching vibrations of quaternary ammonium cations. These characteristic peaks correspond to the -CH2-, benzene ring skeleton, and quaternary ammonium cation groups in the crosslinked structure, respectively, confirming that the membrane material prepared in Example 1 possesses the typical chemical structure of anion exchange membranes, indicating that it has been successfully prepared.
[0120] The present invention has been described in detail with reference to the above embodiments. It should be noted that the above embodiments are merely illustrative examples. Without departing from the spirit and essence of the present invention, those skilled in the art can devise various alternatives and improvements to the present invention, all of which should be understood to be within the scope of protection of the present invention.
Claims
1. A cross-linked anion exchange membrane, characterized in that: The cross-linked anion exchange membrane is obtained by cross-linking quaternized polyarylepiperidine containing olefin side chains with a modified polymer, and its structure is shown in the general formula: Where n = 1~6, x = 10%~25%; Ar represents biphenyl, para-terphenyl, meta-terphenyl, or fluorene; Polymers are polyvinyl chloride, polyethersulfone, polysulfone, polyphenylene ether, polyetheretherketone or polyarylpiperidine; QA is trimethylamine, N-methylpiperidine, N-methylpyrrole, N-methylimidazolium or pyridine; The anion is OH - Cl - or I - .
2. The cross-linked anion exchange membrane according to claim 1, characterized in that: x can take values of 10%, 15%, 20%, or 25%.
3. A cross-linked anion exchange membrane according to claim 1 or 2, characterized in that: The quaternized polyarylepiperidine containing olefin side chains is obtained by polycondensation of biphenyl monomers with 1-methyl-4-piperidinone to obtain polyarylepiperidine, followed by quaternization after grafting with a haloolefin; the biphenyl monomers are selected from one of biphenyl, p-terphenyl, m-terphenyl or fluorene. The modified polymer is obtained by grafting alkenyl imidazole onto a polymer backbone and then quaternizing it. The polymer backbone is selected from one of polyvinyl chloride, polyethersulfone polymers, polysulfone polymers, polyphenylene ether polymers, polyether ether ketone polymers, or polyarylpiperidine polymers.
4. A method for preparing a cross-linked anion exchange membrane according to any one of claims 1 to 3, characterized in that, Includes the following steps: 1) Dissolve biphenyl monomers in solvent A, add 1-methyl-4-piperidinone and catalyst sequentially, react at 0°C to obtain a viscous liquid, precipitate and wash to obtain polyarylpiperidine, and dry for later use; 2) Dissolve the polyarylpiperidine obtained in step 1) in solvent B, add haloolefin and potassium carbonate, react under heating conditions, and after the reaction is complete, precipitate with solvent to obtain polyarylpiperidine containing olefin side chains. 3) Dissolve the polyarylpiperidine containing olefin side chains obtained in step 2) in solvent C, add iodomethane, react in the dark, and after the reaction is complete, precipitate with solvent to obtain quaternized polyarylpiperidine containing olefin side chains. 4) Dissolve the polymer backbone in solvent D, add alkenyl imidazole monomers and potassium carbonate, react under heating conditions, and after the reaction is complete, precipitate with solvent to obtain the modified polymer backbone-imidazole. 5) Dissolve the product obtained in step 4) in solvent E, add quaternizing reagent, react at room temperature, and after the reaction is completed, precipitate with solvent to obtain the modified polymer; 6) Dissolve the quaternized polyarylepiperidine with olefin side chains obtained in step 3) and the modified polymer obtained in step 5) in solvent F, add initiator 2,2-azobisisobutyronitrile to obtain a homogeneous casting solution, and cast it into a film; after film formation, perform anion exchange to obtain the cross-linked anion exchange membrane.
5. The method for preparing a cross-linked anion exchange membrane according to claim 4, characterized in that, Solvent A is selected from one of dichloromethane, 1,2-dichloroethane, and trichloromethane; solvents B to F are each selected from at least one of dimethyl sulfoxide, N-methylpyrrolidone, N,N-dimethylformamide, and N,N-dimethylacetamide.
6. The method for preparing a cross-linked anion exchange membrane according to claim 5, characterized in that, The viscous liquid in step 1) is precipitated with a sodium hydroxide solution with a concentration of 1~3 mol / L; In steps 2) and 3), the precipitation solvent is selected from at least one of n-hexane, cyclohexane, ethyl acetate, and tert-butyl methyl ether; In steps 4) and 5), the precipitation solvent is selected from at least one of methanol, ethanol and acetonitrile.
7. The method for preparing a cross-linked anion exchange membrane according to claim 6, characterized in that, The haloalkene mentioned in step 2) is selected from one of the following: bromopropene, 4-bromo-1-butene, 5-bromo-1-pentene, 6-bromo-1-hexene, 7-bromo-1-heptene, and 8-bromo-1-octene; The alkenyl imidazolium monomer mentioned in step 4) is selected from one of 1-vinylimidazolium and N-propenylimidazolium; The quaternizing agent mentioned in step 5) is selected from one of trimethylamine, N-methylpiperidine, N-methylpyrrole, N-methylimidazolium and pyridine.
8. The method for preparing a cross-linked anion exchange membrane according to claim 7, characterized in that, In step 1), the molar ratio of biphenyl monomers to 1-methyl-4-piperidinone is 1:(1~1.5); In step 2), the molar ratio of polyarylpiperidine to haloalkene is 1:(0.25~0.5); the reaction temperature is 80℃ and the reaction time is 24~48h. In step 3), the molar ratio of polyarylpiperidine containing olefin side chains to iodomethane is 1:(1~1.3); the reaction time is 24~72h; In step 4), the molar ratio of the polymer backbone to the alkenyl imidazole monomer is 1:(0.25~0.5), the reaction temperature is 80℃, and the reaction time is 24~48h. In step 5), the molar ratio of the modified polymer backbone-imidazole to the quaternizing agent is 1:(0.25~0.5), the reaction temperature is room temperature, and the reaction time is 24~48h; In step 6), the molar ratio of the quaternized polyarylepiperidine with olefin side chains obtained in step 3) to the modified polymer obtained in step 5) is 1:(1~1.2).
9. A method for preparing a cross-linked anion exchange membrane according to any one of claims 5 to 8, characterized in that, The catalyst in step 1) is trifluoroacetic acid and trifluoromethanesulfonic acid, and the molar ratio of the biphenyl monomer, trifluoroacetic acid and trifluoromethanesulfonic acid is 1:(1~1.3):(1~10).
10. An application of the cross-linked anion exchange membrane according to any one of claims 1 to 3, characterized in that, The application is in the field of electrodialysis.